2019
DOI: 10.1111/jfpp.14183
|View full text |Cite
|
Sign up to set email alerts
|

Combined drying of Nopal pads ( Opuntia ficus‐indica ): Optimization of osmotic dehydration as a pretreatment before hot air drying

Abstract: The aim of this work was to optimize the osmotic dehydration (OD) as a pretreatment before hot air drying (HAD) in Nopal pads. A Box–Behnken experimental design was used to optimize the OD conditions with respect to physicochemical and chromatic parameters, and mechanical properties of Nopal pads. Factors studied were: Three concentrations of sucrose (30, 40, and 50°Brix), calcium lactate (1, 2, and3%), and immersion time (1.5, 2.5, and 3.5 hr). Results showed that sucrose concentration and immersion time were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Total colour difference Total colour difference of the fresh and osmodehydrated samples was determined using a colorimeter (Konica Minolta Chromameter, Model CR 400/410, Japan) with illuminant D65, 2°observer angle and calibrated using a standard white tile. The system selected was CIE L* a* b* (Rodriguez et al, 2019). Twentyfour pear cubes were measured for each treatment.…”
Section: Quality Analysismentioning
confidence: 99%
“…Total colour difference Total colour difference of the fresh and osmodehydrated samples was determined using a colorimeter (Konica Minolta Chromameter, Model CR 400/410, Japan) with illuminant D65, 2°observer angle and calibrated using a standard white tile. The system selected was CIE L* a* b* (Rodriguez et al, 2019). Twentyfour pear cubes were measured for each treatment.…”
Section: Quality Analysismentioning
confidence: 99%
“…According to literature data, fresh tomato juice has a pH in the range of 4.05 to 4.65 (Ağçam et al, 2018), however, commercial juices were also reported to have a pH of 3.6 ± 0.1 (Zhu et al, 2018) which is in line with the juice used in the study. Research conducted by Rodrigues et al showed that pretreatment of the OS, carried out to optimize the OD process favorably affects the quality of samples that are further dried after OD (Rodriguez et al, 2019). Therefore, the pH of tomato juice was gradually lowered in this study from pH = 3.5 ± 0.1 to pH = 2.0 ± 0.1 in OSs before OD to investigate the effect of pH on the OD kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…showed that pretreatment of the OS, carried out to optimize the OD process favorably affects the quality of samples that are further dried after OD (Rodriguez et al, 2019). Therefore, the pH of tomato juice was gradually lowered in this study from pH = 3.5 ± 0.1 to pH = 2.0 ± 0.1 in OSs before OD to investigate the effect of pH on the OD kinetics.…”
Section: Osmotic Solutionmentioning
confidence: 98%
“…Furthermore, the dry product has advantages such as smaller volume, ease of distribution, year-round availability, and low perishability (Braga et al, 2009). Although there are several ways to dry food, drying with heated air is the most traditional method (Rodriguez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%